Final Year Student Dynamics in the Perspective of Social Support and Academic Reciprocity - Prihatin, Julia Tri Rejeki; Suhesty, Aulia (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
This study aims to determine the correlation between social support and academic resilience in final year students working on their undergraduate thesis. This research method uses a quantitative approach. The subjects in this study were 100 final year students working on their undergraduate thesis at the Faculty of Social and Political Sciences, Mulawarman University using a purposive sampling technique. The data collection method used is the scale of academic resilience and social support. The data analysis technique used is the Pearson Product Moment statistical correlation test. The result showed that there was a significant correlation between social support and academic resilience in final level students working on undergraduate thesis with a value of r count 0.508 > r table 0.197 and a sig value of 0.000 (p < 0.05) which indicates that there is a positive correlation. The higher social support, the higher academic resilience, otherwise the lower the social support, the lower the academic resilience in final level students working on undergraduate thesis.Penelitian ini bertujuan untuk mengetahui hubungan dukungan sosial dengan resiliensi akademik pada mahasiswa tingkat akhir yang mengerjakan skripsi. Metode penelitian ini menggunakan pendekatan kuantitatif. Subjek dalam penelitian ini 100 mahasiswa tingkat akhir yang mengerjakan skripsi di Fakultas Ilmu Sosial dan Ilmu Politik Universitas Mulawarman dengan menggunakan teknik purposive sampling. Metode pengumpulan data yang digunakan adalah dengan skala resiliensi akademik dan dukungan sosial. Teknik analisis data yang digunakan adalah uji statistik korelasi Pearson Product Moment. Hasil penelitian ini menunjukkan bahwa terdapat hubungan yang signifikan antara dukungan sosial dengan resiliensi akademik pada mahasiswa tingkat akhir yang mengerjakan skripsi dengan nilai r hitung 0.508 > r tabel 0.197 dan nilai sig 0.000 (p < 0.05) yang menunjukkan bahwa ada hubungan dengan arah positif. Artinya semakin tinggi dukungan sosial, maka semakin tinggi resiliensi akademik, dan sebaliknya semakin rendah dukungan sosial, maka semakin rendah resiliensi akademik pada mahasiswa tingkat akhir yang mengerjakan skripsi.